Preparation method and application of wear-resistant TPE material for data line
Wear-resistant TPE materials are prepared by using reinforced monomers and modified fillers produced by specific reactions in the data line, combined with ethylenediamine, which solves the problem of wear and fracture of the data line surface and improves wear resistance and service life .
Patent Information
- Application Number
- CN202411624653.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
At this stage, the data cable is prone to surface wear or even breakage after long-term use.
Fluorocyclic tetrasiloxane, octafluoropenyl allyl ether, chloroplatinic acid and other materials are reacted under specific conditions to obtain fluorocyclic tetrasiloxane, and polymerize with other materials to form a strengthened monomer and the modified filler, and finally ethylenediamine is added to produce a wear-resistant TPE material.
It improves the wear resistance and service life of the data cable, while maintaining the toughness and bending resistance of the material.
Smart Images

Figure BDA0005134398750000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wear-resistant TPE material preparation, and in particular to a preparation method and application of a wear-resistant TPE material for a data cable. Background Art
[0002] With the popularization and diversification of electronic devices, data cables, as a common connection tool, are used more frequently and in a wider range of working environments. Traditional data cables, especially when connecting mobile phones, tablets and other devices, often need to withstand certain friction and external forces due to frequent plugging and unplugging. Therefore, improving the durability and wear resistance of data cables has become the key to improving user experience and extending product life. TPE material, that is, thermoplastic elastomer, is a material with high elasticity, high strength, and high resilience of rubber, and can be injection molded. It is environmentally friendly and non-toxic, has a wide range of hardness, and has excellent colorability, soft touch, and excellent weather resistance, fatigue resistance and temperature resistance. However, its wear resistance is not high. At this stage, the way to enhance wear resistance is to add wear-resistant fillers, but the addition of wear-resistant fillers reduces its bending resistance, thereby reducing its service life. Summary of the invention
[0003] The purpose of the present invention is to provide a preparation method of a wear-resistant TPE material for a data cable and its application, which solves the problem that the surface of the data cable will be worn or even broken after long-term use at this stage.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a wear-resistant TPE material for a data cable, specifically comprising the following steps:
[0006] Step A1: Tetramethylcyclotetrasiloxane, octafluoropentyl allyl ether, chloroplatinic acid and DMF are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 120-150 r / min and a temperature of 70-80° C. to obtain fluorinated cyclotetrasiloxane; octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 120-150 r / min and a temperature of 105-110° C. to obtain a reinforced monomer;
[0007] Step A2: Mix polyether polyol, isophorone diisocyanate, dibutyltin dilaurate and DMF, introduce nitrogen protection, react for 2-3 hours at a speed of 60-80r / min and a temperature of 75-80°C, add reinforcing monomer and modified filler, react for 3-4 hours, add ethylenediamine, react for 1-1.5 hours, heat to 100°C, keep warm for 1-1.5 hours, cool to 40-50°C, keep warm for 10-15 hours, and obtain wear-resistant TPE material for data cables.
[0008] Furthermore, the molar ratio of tetramethylcyclotetrasiloxane and octafluoropentyl allyl ether described in step A1 is 1:4, the amount of chloroplatinic acid used is 1‰ of the mass of octafluoropentyl allyl ether, and the molar ratio of octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.9:0.5:3:2.
[0009] Furthermore, the mass ratio of the polyether polyol, isophorone diisocyanate, reinforcing monomer, modified filler and ethylenediamine described in step A2 is 12:42:20:5:5, the amount of dibutyltin dilaurate is 1.5% of the mass of isophorone diisocyanate, and the molecular weight of the polyether polyol is 2000.
[0010] Further, the modified filler is prepared by the following steps:
[0011] Step B1: Sodium imidazole, 3-chloropropyltrimethoxysilane and toluene are mixed, and reacted for 3-5 hours at a speed of 200-300 r / min and a temperature of 10-15° C. to obtain a modified monomer; the modified monomer, isopropanol, sodium hydroxide and deionized water are mixed, and reacted for 3-5 hours at a speed of 150-200 r / min and a temperature of 85-90° C., and then cooled to 20-25° C. and reacted for 10-15 hours to obtain functionalized cyclotetrasiloxane sodium tetrasiloxide;
[0012] Step B2: Methyldichlorosilane, allyl alcohol, chloroplatinic acid and DMF are mixed, nitrogen is introduced for protection, and the reaction is carried out for 8-10 hours at a speed of 120-150 r / min and a temperature of 70-80° C. to obtain intermediate 1; intermediate 1, 3-furoic acid, p-toluenesulfonic acid and toluene are introduced for protection with nitrogen, and the reaction is carried out for 3-5 hours at a speed of 200-300 r / min and a temperature of 110-120° C. to obtain a modifier; functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine and tetrahydrofuran are mixed, and the modifier is added under stirring at a speed of 150-200 r / min and a temperature of 0° C., and the reaction is carried out for 3-5 hours, and then the temperature is raised to 20-25° C. and the reaction is carried out for 20-24 hours to obtain a functionalized cage-type silsesquioxane;
[0013] Step B3: dispersing graphene in ethanol, stirring and adding deionized water and KH550 at a speed of 200-300 r / min and a temperature of 60-70°C, reacting for 2-3 hours to obtain pretreated graphene, mixing the pretreated graphene, maleic anhydride and DMF, reacting for 1-1.5 hours at a speed of 150-200 r / min and a temperature of 10-15°C, heating to 60-65°C, adding triethylamine, acetic anhydride and nickel acetate, and continuing the reaction for 2-3 hours to obtain modified graphene;
[0014] Step B4: The modified graphene, functionalized cage silsesquioxane, aluminum chloride and DMF are mixed evenly, and the reaction is carried out at a speed of 120-150r / min and a temperature of 50-60°C for 8-10h to obtain a precursor. The precursor, 1-(3-aminopropyl)imidazole and methanol are mixed evenly, and the reaction is carried out at a speed of 200-300r / min and a temperature of 30-40°C. Zinc chloride is added while stirring, and the temperature is raised to 60-65°C. The reaction is carried out for 3-5h to obtain a modified filler.
[0015] Furthermore, the molar ratio of sodium imidazole and 3-chloropropyltrimethoxysilane in step B1 is 1:1, and the usage ratio of the modified monomer, isopropanol, sodium hydroxide and deionized water is 5mmol:10mL:6mmol:5mmol.
[0016] Furthermore, the molar ratio of methyldichlorosilane and acryl alcohol described in step B2 is 1:1, the amount of chloroplatinic acid used is 1‰ of the mass of methyldichlorosilane, the molar ratio of intermediate 1 and 3-furoic acid is 1:1, the mass of p-toluenesulfonic acid is 3% of 3-furoic acid, and the mass ratio of functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine, tetrahydrofuran and modifier is 20:4:40:5.
[0017] Further, the amount of KH550 described in step B3 is 1% of the mass of graphene, and the amount ratio of pretreated graphene, DMF, maleic anhydride, triethylamine, acetic anhydride and nickel acetate is 5g:50mL:50mmol:5mL:12mL:3.5g.
[0018] Furthermore, the mass ratio of the modified graphene and the functionalized cage-type silsesquioxane described in step B4 is 3:1, the mass of aluminum chloride is 8‰ of the mass of the modified graphene, and the amount ratio of the precursor, 1-(3-aminopropyl)imidazole and zinc chloride is 1g:20mmol:5mmol.
[0019] Beneficial effects of the present invention: A wear-resistant TPE material for a data line prepared by the present invention uses tetramethylcyclotetrasiloxane and octafluoropentyl allyl ether as raw materials, and under the action of chloroplatinic acid, Si-H on the tetramethylcyclotetrasiloxane reacts with double bonds on the octafluoropentyl allyl ether to obtain fluorinated cyclotetrasiloxane, the octamethylcyclotetrasiloxane and the fluorinated cyclotetrasiloxane are ring-opened, and then polymerized with 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to obtain a reinforcing monomer, polyether polyol and isophorone diisocyanate are reacted to form a polyurethane prepolymer, the reinforcing monomer and the modified filler are added, the amino group on the reinforcing monomer and the amino group on the surface of the modified filler can extend the chain of the polyurethane prepolymer, and finally ethylenediamine is added to obtain the wear-resistant TPE material.
[0020] The modified filler uses sodium imidazole and 3-chloropropyltrimethoxysilane as raw materials, so that sodium imidazole is grafted to the chlorine atom site on 3-chloropropyltrimethoxysilane to obtain a modified monomer, and the modified monomer is hydrolyzed and polycondensed to form functionalized sodium tetrasiloxane tetrasilanol, and methyldichlorosilane and allyl alcohol react with the Si-H bond on methyldichlorosilane and the double bond on allyl alcohol under the action of chloroplatinic acid to obtain an intermediate 1, and the intermediate 1 and 3-furoic acid are esterified under the action of p-toluenesulfonic acid, so that the hydroxyl group on the intermediate 1 reacts with the carboxyl group on the 3-furoic acid to obtain a modifier, and the functionalized sodium tetrasiloxane tetrasilanol reacts with the modifier to react the silanol on the functionalized sodium tetrasiloxane tetrasilanol Sodium reacts with chlorine atom sites on a modifier to obtain functionalized cage-type silsesquioxane; graphene is treated with KH550 to graft amino groups on the graphene surface to obtain pretreated graphene; the pretreated graphene is reacted with maleic anhydride to react the amino groups on the pretreated graphene with maleic anhydride to form maleimide to obtain modified graphene; the modified graphene and functionalized cage-type silsesquioxane are reacted with aluminum trichloride to react the maleimide on the functionalized graphene with the furan structure DA on the functionalized cage-type silsesquioxane to obtain a precursor; the precursor, 1-(3-aminopropyl)imidazole and zinc chloride are reacted to coat the surface of the precursor with imidazole zinc to obtain a modified filler.
[0021] The TPE material has a hyperbranched structure that can increase the mechanical properties of the material. The addition of modified fillers increases the cross-linking points of the TPE material, allowing the TPE material molecules to form a stable grid, thereby increasing the wear resistance of the TPE material. The addition of reinforcing monomers embeds silicone segments and fluorocarbon segments in the molecular chain, increasing the hydrophobicity of the TPE molecules and improving the service life. The modified filler is connected to the polyurethane prepolymer molecular chain with a zinc organic framework, and the TPE material itself contains a six-membered ring structure, so that when the TPE material is worn, it can adapt well to surface contact, thereby reducing wear. The dynamic cross-linking of the modified filler and the TPE material molecules improves the toughness of the material, and the toughness will not be greatly reduced due to the increase in cross-linking points, thereby increasing the bending resistance of the TPE material. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Embodiment 1: A method for preparing a wear-resistant TPE material for a data cable, comprising the following steps:
[0024] Step A1: Tetramethylcyclotetrasiloxane, octafluoropentyl allyl ether, chloroplatinic acid and DMF are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 3 hours at a speed of 120 r / min and a temperature of 70° C. to obtain fluorinated cyclotetrasiloxane; octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 3 hours at a speed of 120 r / min and a temperature of 105° C. to obtain a reinforcing monomer;
[0025] Step A2: Mix polyether polyol, isophorone diisocyanate, dibutyltin dilaurate and DMF, introduce nitrogen protection, react for 2 hours at a speed of 60r / min and a temperature of 75°C, add reinforcing monomers and modified fillers, react for 3 hours, add ethylenediamine, react for 1 hour, heat to 100°C, keep warm for 1 hour, cool to 40°C, keep warm for 10 hours, and obtain wear-resistant TPE material for data cables.
[0026] The molar ratio of tetramethylcyclotetrasiloxane and octafluoropentyl allyl ether described in step A1 is 1:4, the amount of chloroplatinic acid used is 1‰ of the mass of octafluoropentyl allyl ether, and the molar ratio of octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.9:0.5:3:2.
[0027] The mass ratio of the polyether polyol, isophorone diisocyanate, reinforcing monomer, modified filler and ethylenediamine described in step A2 is 12:42:20:5:5, the amount of dibutyltin dilaurate is 1.5% of the mass of isophorone diisocyanate, and the molecular weight of the polyether polyol is 2000.
[0028] The modified filler is prepared by the following steps:
[0029] Step B1: Sodium imidazole, 3-chloropropyltrimethoxysilane and toluene are mixed, and reacted at a speed of 200 r / min and a temperature of 10° C. for 3 hours to obtain a modified monomer; the modified monomer, isopropanol, sodium hydroxide and deionized water are mixed, and reacted at a speed of 150 r / min and a temperature of 85° C. for 3 hours, and then cooled to 20° C. and reacted for 10 hours to obtain functionalized cyclotetrasiloxane sodium tetrasiloxide;
[0030] Step B2: Methyldichlorosilane, allyl alcohol, chloroplatinic acid and DMF are mixed, nitrogen is introduced for protection, and the reaction is carried out for 8 hours at a speed of 120 r / min and a temperature of 70°C to obtain intermediate 1. Intermediate 1, 3-furoic acid, p-toluenesulfonic acid and toluene are introduced for protection with nitrogen, and the reaction is carried out for 3 hours at a speed of 200 r / min and a temperature of 110°C to obtain a modifier. Functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine and tetrahydrofuran are mixed, and the modifier is added under stirring at a speed of 150 r / min and a temperature of 0°C. After reacting for 3 hours, the temperature is raised to 20°C and the reaction is carried out for 20 hours to obtain a functionalized cage-type silsesquioxane;
[0031] Step B3: dispersing graphene in ethanol, stirring and adding deionized water and KH550 at a speed of 200 r / min and a temperature of 60°C, reacting for 2 hours to obtain pretreated graphene, mixing the pretreated graphene, maleic anhydride and DMF, reacting for 1 hour at a speed of 150 r / min and a temperature of 10°C, heating to 60°C, adding triethylamine, acetic anhydride and nickel acetate, and continuing the reaction for 2 hours to obtain modified graphene;
[0032] Step B4: Evenly mix the modified graphene, functionalized cage-type silsesquioxane, aluminum chloride and DMF, and react at a speed of 120 r / min and a temperature of 50°C for 8 hours to obtain a precursor; evenly mix the precursor, 1-(3-aminopropyl)imidazole and methanol, and stir and add zinc chloride at a speed of 200 r / min and a temperature of 30°C; raise the temperature to 60°C, and react for 3 hours to obtain a modified filler.
[0033] The molar ratio of sodium imidazole and 3-chloropropyltrimethoxysilane in step B1 is 1:1, and the amount ratio of the modified monomer, isopropanol, sodium hydroxide and deionized water is 5mmol:10mL:6mmol:5mmol.
[0034] The molar ratio of methyldichlorosilane and acryl alcohol described in step B2 is 1:1, the amount of chloroplatinic acid used is 1‰ of the mass of methyldichlorosilane, the molar ratio of intermediate 1 and 3-furoic acid is 1:1, the mass of p-toluenesulfonic acid is 3% of 3-furoic acid, and the mass ratio of functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine, tetrahydrofuran and modifier is 20:4:40:5.
[0035] The amount of KH550 described in step B3 is 1% of the mass of graphene, and the amount ratio of pretreated graphene, DMF, maleic anhydride, triethylamine, acetic anhydride and nickel acetate is 5g:50mL:50mmol:5mL:12mL:3.5g.
[0036] The mass ratio of the modified graphene and the functionalized cage-type silsesquioxane described in step B4 is 3:1, the mass of aluminum chloride is 8‰ of the mass of the modified graphene, and the amount ratio of the precursor, 1-(3-aminopropyl)imidazole and zinc chloride is 1g:20mmol:5mmol.
[0037] Embodiment 2: A method for preparing a wear-resistant TPE material for a data cable, comprising the following steps:
[0038] Step A1: Tetramethylcyclotetrasiloxane, octafluoropentyl allyl ether, chloroplatinic acid and DMF are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 4 hours at a speed of 120 r / min and a temperature of 75° C. to obtain fluorinated cyclotetrasiloxane; octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out at a speed of 120 r / min and a temperature of 110° C. to obtain a reinforcing monomer;
[0039] Step A2: Mix polyether polyol, isophorone diisocyanate, dibutyltin dilaurate and DMF, introduce nitrogen protection, react for 2.5 hours at a speed of 60r / min and a temperature of 80°C, add reinforcing monomer and modified filler, react for 3 hours, add ethylenediamine, react for 1.5 hours, heat to 100°C, keep warm for 1 hour, cool to 45°C, keep warm for 13 hours, and obtain wear-resistant TPE material for data cables.
[0040] The molar ratio of tetramethylcyclotetrasiloxane and octafluoropentyl allyl ether described in step A1 is 1:4, the amount of chloroplatinic acid used is 1‰ of the mass of octafluoropentyl allyl ether, and the molar ratio of octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.9:0.5:3:2.
[0041] The mass ratio of the polyether polyol, isophorone diisocyanate, reinforcing monomer, modified filler and ethylenediamine described in step A2 is 12:42:20:5:5, the amount of dibutyltin dilaurate is 1.5% of the mass of isophorone diisocyanate, and the molecular weight of the polyether polyol is 2000.
[0042] The modified filler is prepared by the following steps:
[0043] Step B1: Sodium imidazole, 3-chloropropyltrimethoxysilane and toluene are mixed, and reacted at a speed of 300 r / min and a temperature of 10° C. for 4 hours to obtain a modified monomer; the modified monomer, isopropanol, sodium hydroxide and deionized water are mixed, and reacted at a speed of 150 r / min and a temperature of 90° C. for 4 hours, and then cooled to 25° C. and reacted for 10 hours to obtain functionalized cyclotetrasiloxane sodium tetrasiloxide;
[0044] Step B2: Methyldichlorosilane, allyl alcohol, chloroplatinic acid and DMF are mixed, nitrogen is introduced for protection, and the reaction is carried out for 9 hours at a speed of 150 r / min and a temperature of 75°C to obtain intermediate 1. Intermediate 1, 3-furoic acid, p-toluenesulfonic acid and toluene are introduced for protection with nitrogen, and the reaction is carried out for 4 hours at a speed of 200 r / min and a temperature of 115°C to obtain a modifier. Functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine and tetrahydrofuran are mixed, and the modifier is added under stirring at a speed of 200 r / min and a temperature of 0°C. After reacting for 4 hours, the temperature is raised to 25°C and the reaction is carried out for 24 hours to obtain a functionalized cage-type silsesquioxane;
[0045] Step B3: dispersing graphene in ethanol, stirring and adding deionized water and KH550 at a speed of 200 r / min and a temperature of 65°C, reacting for 3 hours to obtain pretreated graphene, mixing the pretreated graphene, maleic anhydride and DMF, reacting for 1 hour at a speed of 150 r / min and a temperature of 15°C, heating to 65°C, adding triethylamine, acetic anhydride and nickel acetate, and continuing the reaction for 2 hours to obtain modified graphene;
[0046] Step B4: Evenly mix the modified graphene, functionalized cage-type silsesquioxane, aluminum chloride and DMF, and react at a speed of 150 r / min and a temperature of 55°C for 9 hours to obtain a precursor; evenly mix the precursor, 1-(3-aminopropyl)imidazole and methanol, and stir and add zinc chloride at a speed of 200 r / min and a temperature of 35°C; raise the temperature to 65°C, and react for 4 hours to obtain a modified filler.
[0047] The molar ratio of sodium imidazole and 3-chloropropyltrimethoxysilane in step B1 is 1:1, and the amount ratio of the modified monomer, isopropanol, sodium hydroxide and deionized water is 5mmol:10mL:6mmol:5mmol.
[0048] The molar ratio of methyldichlorosilane and acryl alcohol described in step B2 is 1:1, the amount of chloroplatinic acid used is 1‰ of the mass of methyldichlorosilane, the molar ratio of intermediate 1 and 3-furoic acid is 1:1, the mass of p-toluenesulfonic acid is 3% of 3-furoic acid, and the mass ratio of functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine, tetrahydrofuran and modifier is 20:4:40:5.
[0049] The amount of KH550 described in step B3 is 1% of the mass of graphene, and the amount ratio of pretreated graphene, DMF, maleic anhydride, triethylamine, acetic anhydride and nickel acetate is 5g:50mL:50mmol:5mL:12mL:3.5g.
[0050] The mass ratio of the modified graphene and the functionalized cage-type silsesquioxane described in step B4 is 3:1, the mass of aluminum chloride is 8‰ of the mass of the modified graphene, and the amount ratio of the precursor, 1-(3-aminopropyl)imidazole and zinc chloride is 1g:20mmol:5mmol.
[0051] Embodiment 3: A method for preparing a wear-resistant TPE material for a data cable, comprising the following steps:
[0052] Step A1: Tetramethylcyclotetrasiloxane, octafluoropentyl allyl ether, chloroplatinic acid and DMF are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out at a speed of 150 r / min and a temperature of 80° C. for 5 hours to obtain fluorinated cyclotetrasiloxane; octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out at a speed of 150 r / min and a temperature of 110° C. for 5 hours to obtain a reinforcing monomer;
[0053] Step A2: Mix polyether polyol, isophorone diisocyanate, dibutyltin dilaurate and DMF, introduce nitrogen protection, react for 3 hours at a speed of 80r / min and a temperature of 80°C, add reinforcing monomer and modified filler, react for 4 hours, add ethylenediamine, react for 1.5 hours, heat to 100°C, keep warm for 1.5 hours, cool to 50°C, keep warm for 15 hours, and obtain wear-resistant TPE material for data cables.
[0054] The molar ratio of tetramethylcyclotetrasiloxane and octafluoropentyl allyl ether described in step A1 is 1:4, the amount of chloroplatinic acid used is 1‰ of the mass of octafluoropentyl allyl ether, and the molar ratio of octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.9:0.5:3:2.
[0055] The mass ratio of the polyether polyol, isophorone diisocyanate, reinforcing monomer, modified filler and ethylenediamine described in step A2 is 12:42:20:5:5, the amount of dibutyltin dilaurate is 1.5% of the mass of isophorone diisocyanate, and the molecular weight of the polyether polyol is 2000.
[0056] The modified filler is prepared by the following steps:
[0057] Step B1: Sodium imidazole, 3-chloropropyltrimethoxysilane and toluene are mixed, and reacted at a speed of 300 r / min and a temperature of 15° C. for 5 hours to obtain a modified monomer; the modified monomer, isopropanol, sodium hydroxide and deionized water are mixed, and reacted at a speed of 200 r / min and a temperature of 90° C. for 5 hours, and then cooled to 25° C. and reacted for 15 hours to obtain functionalized cyclotetrasiloxane sodium tetrasiloxide;
[0058] Step B2: Methyldichlorosilane, allyl alcohol, chloroplatinic acid and DMF are mixed, nitrogen is introduced for protection, and the reaction is carried out for 10 hours at a speed of 150 r / min and a temperature of 80°C to obtain intermediate 1. Intermediate 1, 3-furoic acid, p-toluenesulfonic acid and toluene are introduced for protection with nitrogen, and the reaction is carried out for 5 hours at a speed of 300 r / min and a temperature of 120°C to obtain a modifier. Functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine and tetrahydrofuran are mixed, and the modifier is added under stirring at a speed of 200 r / min and a temperature of 0°C. After reacting for 5 hours, the temperature is raised to 25°C and the reaction is carried out for 24 hours to obtain a functionalized cage-type silsesquioxane;
[0059] Step B3: dispersing graphene in ethanol, stirring and adding deionized water and KH550 at a speed of 300 r / min and a temperature of 70°C, reacting for 3 hours to obtain pretreated graphene, mixing the pretreated graphene, maleic anhydride and DMF, reacting for 1.5 hours at a speed of 200 r / min and a temperature of 15°C, heating to 65°C, adding triethylamine, acetic anhydride and nickel acetate, and continuing the reaction for 2-3 hours to obtain modified graphene;
[0060] Step B4: Evenly mix the modified graphene, functionalized cage-type silsesquioxane, aluminum chloride and DMF, and react at a speed of 150 r / min and a temperature of 60°C for 10 hours to obtain a precursor; evenly mix the precursor, 1-(3-aminopropyl)imidazole and methanol, and stir at a speed of 300 r / min and a temperature of 40°C, add zinc chloride, raise the temperature to 65°C, and react for 5 hours to obtain a modified filler.
[0061] The molar ratio of sodium imidazole and 3-chloropropyltrimethoxysilane in step B1 is 1:1, and the amount ratio of the modified monomer, isopropanol, sodium hydroxide and deionized water is 5mmol:10mL:6mmol:5mmol.
[0062] The molar ratio of methyldichlorosilane and acryl alcohol described in step B2 is 1:1, the amount of chloroplatinic acid used is 1‰ of the mass of methyldichlorosilane, the molar ratio of intermediate 1 and 3-furoic acid is 1:1, the mass of p-toluenesulfonic acid is 3% of 3-furoic acid, and the mass ratio of functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine, tetrahydrofuran and modifier is 20:4:40:5.
[0063] The amount of KH550 described in step B3 is 1% of the mass of graphene, and the amount ratio of pretreated graphene, DMF, maleic anhydride, triethylamine, acetic anhydride and nickel acetate is 5g:50mL:50mmol:5mL:12mL:3.5g.
[0064] The mass ratio of the modified graphene and the functionalized cage-type silsesquioxane described in step B4 is 3:1, the mass of aluminum chloride is 8‰ of the mass of the modified graphene, and the amount ratio of the precursor, 1-(3-aminopropyl)imidazole and zinc chloride is 1g:20mmol:5mmol.
[0065] Comparative Example 1: Compared with Example 1, no reinforcing monomer was added to this comparative example, and the remaining steps were the same.
[0066] Comparative Example 2: Compared with Example 1, this comparative example uses phenyltrimethoxysilane instead of the modified monomer, and the other steps are the same.
[0067] Comparative Example 3: Compared with Example 1, this comparative example uses pretreated graphene instead of modified filler, and the remaining steps are the same.
[0068] Comparative Example 4. Compared with Example 1, 1-(3-aminopropyl)imidazole and methanol are mixed evenly, stirred at a speed of 200 r / min and a temperature of 30°C, zinc chloride is added, the temperature is raised to 60°C, and the reaction is carried out for 3 hours. The obtained product replaces the modified filler, and the remaining steps are the same.
[0069] Comparative Example 5: Compared with Example 1, this comparative example uses functionalized cage-type silsesquioxane instead of the precursor, and the remaining steps are the same.
[0070] The TPE materials prepared in Examples 1-3 and Comparative Examples 1-5 were tested for wear resistance according to the standard of GB / T3960-2016, and 30 mm×5 mm×2 mm specimens were prepared according to the standard of GB / T1040.1-2018, with a tensile rate of 5 mm / min, and the tensile strength was tested. The test results are shown in Table 1 below;
[0071] Table 1
[0072]
[0073]
[0074] It can be seen from the above table that the present invention has excellent toughness while maintaining good wear resistance.
[0075] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a wear-resistant TPE material for a data cable, characterized in that: The specific steps include: Step A1: Tetramethylcyclotetrasiloxane, octafluoropentyl allyl ether, chloroplatinic acid and DMF are uniformly mixed, nitrogen is introduced for protection, and a reaction is carried out to obtain fluorinated cyclotetrasiloxane; octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and a reaction is carried out to obtain a reinforcing monomer; Step A2: polyether polyol, isophorone diisocyanate, dibutyltin dilaurate and DMF are mixed, nitrogen is introduced for protection, a reaction is carried out, a reinforcing monomer and a modified filler are added, ethylenediamine is added, a reaction is carried out, the temperature is increased and kept, and the temperature is decreased and kept, so as to obtain a wear-resistant TPE material for a data cable.
2. The method for preparing a wear-resistant TPE material for a data cable according to claim 1, characterized in that: The molar ratio of tetramethylcyclotetrasiloxane and octafluoropentyl allyl ether described in step A1 is 1:4, and the molar ratio of octamethylcyclotetrasiloxane, fluorinated cyclotetrasiloxane, tetramethylammonium hydroxide, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.9:0.5:3:
2.
3. The method for preparing a wear-resistant TPE material for a data cable according to claim 1, characterized in that: The mass ratio of the polyether polyol, isophorone diisocyanate, reinforcing monomer, modified filler and ethylenediamine described in step A2 is 12:42:20:5:
5.
4. The method for preparing a wear-resistant TPE material for a data cable according to claim 1, characterized in that: The modified filler is prepared by the following steps: Step B1: sodium imidazole, 3-chloropropyltrimethoxysilane and toluene are mixed and reacted to obtain a modified monomer, and the modified monomer, isopropanol, sodium hydroxide and deionized water are mixed and reacted, and the temperature is lowered to react to obtain functionalized cyclotetrasiloxane sodium tetrasiloxide; Step B2: Methyldichlorosilane, allyl alcohol, chloroplatinic acid and DMF are mixed, nitrogen is introduced to protect, and the reaction is carried out to obtain intermediate 1; intermediate 1, 3-furoic acid, p-toluenesulfonic acid and toluene are introduced into nitrogen to protect, and the reaction is carried out to obtain a modifier; functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine and tetrahydrofuran are mixed and stirred, and the modifier is added, and the reaction is carried out, and the temperature is raised to continue the reaction to obtain a functionalized cage-type silsesquioxane; Step B3: dispersing graphene in ethanol, stirring, adding deionized water and KH550, reacting to obtain pretreated graphene, mixing the pretreated graphene, maleic anhydride and DMF for reaction, heating and adding triethylamine, acetic anhydride and nickel acetate, continuing the reaction to obtain modified graphene; Step B4: The modified graphene, functionalized cage-type silsesquioxane, aluminum chloride and DMF are mixed and reacted to obtain a precursor, the precursor, 1-(3-aminopropyl)imidazole and methanol are mixed and stirred, zinc chloride is added, and the temperature is raised to react to obtain a modified filler.
5. The method for preparing a wear-resistant TPE material for a data cable according to claim 4, characterized in that: The molar ratio of sodium imidazole and 3-chloropropyltrimethoxysilane in step B1 is 1:1, and the amount ratio of the modified monomer, isopropanol, sodium hydroxide and deionized water is 5mmol:10mL:6mmol:5mmol.
6. The method for preparing a wear-resistant TPE material for a data cable according to claim 4, characterized in that: The molar ratio of methyldichlorosilane and allyl alcohol described in step B2 is 1:1, the molar ratio of intermediate 1 and 3-furoic acid is 1:1, and the mass ratio of functionalized cyclotetrasiloxane sodium tetrasiloxide, triethylamine, tetrahydrofuran and modifier is 20:4:40:
5.
7. The method for preparing a wear-resistant TPE material for a data cable according to claim 4, characterized in that: The amount of KH550 described in step B3 is 1% of the mass of graphene, and the amount ratio of pretreated graphene, DMF, maleic anhydride, triethylamine, acetic anhydride and nickel acetate is 5g:50mL:50mmol:5mL:12mL:3.5g.
8. The method for preparing a wear-resistant TPE material for a data cable according to claim 4, characterized in that: The mass ratio of the modified graphene and the functionalized cage-type silsesquioxane described in step B4 is 3:1, and the amount ratio of the precursor, 1-(3-aminopropyl)imidazole and zinc chloride is 1g:20mmol:5mmol.
9. An application of wear-resistant TPE material for data cables, characterized in that: The wear-resistant TPE material prepared by the method described in any one of claims 1 to 8 is used to prepare a data cable.
Citation Information
Patent Citations
Anti-corrosion lining material for high-temperature-resistant and wear-resistant pipeline and preparation method of anti-corrosion lining material
CN118546450A
Formaldehyde-removing composite functional fiber cotton as well as preparation method and application thereof
CN118835471A
Solvent-Free Kraft Lignin and Silsesquioxane Modification for Water-Based Superhydrophobic Wood Coating
US20250101308A1
Anti-electron-radiation garment fabric and preparation method therefor
WO2023123376A1
Scratch-resistant wear-resistant self-extinction waterborne polyurethane emulsion and preparation method therefor
WO2024174411A1
Cited By
Polyurethane foam for heat insulation strip and preparation method of polyurethane foam
CN120737305A